505 Efficacy of Pitolisant in the Treatment of Cataplexy in Adults With Narcolepsy. (3rd May 2021) - Davis, Craig; Zarycranski, Donna; Doliba, Markiyan; Dayno, Jeffrey; Schwartz, Jean-Charles
Abstract: Introduction: Pitolisant was initially approved by the FDA in 2019 for the treatment of excessive daytime sleepiness in adult patients with narcolepsy; in 2020, the indication was expanded to include the treatment of cataplexy. Methods: Cataplexy data from 7- or 8-week, randomized, placebo-controlled studies (HARMONY-CTP, HARMONY-1) are reviewed and summarized. In HARMONY-CTP, all patients were required to have ≥3 cataplexy attacks per week at baseline; HARMONY-1 enrolled patients with narcolepsy with or without cataplexy. Pitolisant was individually titrated to a maximum potential dose of 35.6 mg/day. The weekly (WRC) or daily (DRC) rate of cataplexy attacks was calculated from patient diaries. Results: In HARMONY-CTP (pitolisant, n=54; placebo, n=51), mean baseline WRC was 11.7 in the pitolisant group and 9.6 in the placebo group. In the subset of HARMONY-1 patients with cataplexy (pitolisant, n=17; placebo, n=11), mean baseline DRC was 1.5 and 1.2, respectively. In HARMONY-CTP, least-squares (LS) mean change in WRC was significantly greater for pitolisant versus placebo at Week 2 (-4.1 vs 1.2; P=0.004) and continued through end of treatment (Week 7; -6.5 vs -0.1; P<0.001). In HARMONY-CTP, treatment response was observed in 66.7% of pitolisant-treated versus 25.5% of placebo-treated patients (P<0.001) for WRC reduction ≥50%, and 77.8% versus 33.3% of patients (P<0.001) for WRC reduction ≥25%. In HARMONY-1, LS mean change in DRC was significantly greater for pitolisant versus placebo at Week 5 (-1.04 vs 0.17; P=0.047) and continued through end of treatment (Week 8; -0.96 vs 0.35; P=0.035). In a pooled analysis of patients with high burden of cataplexy (≥15 attacks/week) at baseline (pitolisant, n=20; placebo, n=11), LS mean change in WRC at end-of-treatment assessment was significantly greater for pitolisant (-14.5; baseline, 23.9; final, 9.4) versus placebo (-0.1; baseline, 23.1; final, 23.0; P=0.004). There was no evidence of rebound cataplexy after a 1-week placebo washout period. Conclusion: Pitolisant, at once-daily doses of up to 35.6 mg, demonstrated a statistically significant and clinically meaningful reduction in the frequency of cataplexy attacks in adults with narcolepsy, including patients with a high symptom burden. Onset of response was observed within the first few weeks of pitolisant treatment. Support (if any): Bioprojet Pharma and Harmony Biosciences, LLC.